Mitochondrien unter Stress: die Rolle der Präsequenzprotease MPP - Vögtle, Friederike-Nora (Biospektrum, 2021)
Abstract - The majority of mitochondrial proteins are encoded in the nuclear genome, so that the nearly entire proteome is assembled by post-translational preprotein import from the cytosol. Proteomic imbalances are sensed and induce cellular stress response pathways to restore proteostasis. Here, the mitochondrial presequence protease MPP serves as example to illustrate the critical role of mitochondrial protein biogenesis and proteostasis on cellular integrity.